A supramolecular copolymer based on small molecules, used for a multifunctional adhesive and rapid hemostasis. Issue 41 (6th October 2020) - Chen, Junying; Guo, Dawei; Liang, Shihao; Liu, Zuozhen
Abstract : A multifunctional supramolecular adhesive synthesized using a natural small molecule monomer thioctic acid. Abstract : Modern adhesives usually need to have integrated functions to meet the growing application needs, such as stimulus responsiveness, reversible adhesion ability, self-healing function, and adhesion ability under humid environments. Compared with traditional polymer adhesive materials, supramolecular adhesive materials made by self-assembly of small molecular monomers are rarely explored. Here, inspired by the conversion of thioctic acid (TA) from small molecular biological sources into high-performance supramolecular polymeric materials, catechol groups were grafted on thioctic acid and polyethylene glycol diacrylate (PEGDA) was introduced. TADP30 supramolecular adhesive material was successfully constructed. TADP30 achieves fast waterproof adhesion to a variety of substrates and is reusable. The self-healing ability comes from the dynamic disulfide bond between TADP30 molecules, which has high-efficiency self-healing ability (more than 80% tensile recovery within 1 hour). The benign structural unit of TADP30 makes it have low toxicity. In addition, a large number of catechol groups on the TADP chain endowed the adhesive with tissue adhesion properties and cell affinity. We expanded its biomedical applications by performing wound healing experiments with mouse liver injury models. The wound healing experiments proved that TADP30 has healing function and good in vivo compatibility. Compared with the control group, the total blood loss of the TADP30 adhesive group in the mouse liver injury model was reduced by nearly 70%. From multifunctional bonding to tissue healing and wound hemostasis, the polymer is expected to become a new type of adhesive material.